Homeostasis of the Naive CD4(+) T Cell Compartment during Aging - Kilpatrick, Ryan D. (2008)
Despite thymic involution, the number of naive CD4(+) T cells diminishes slowly during aging, suggesting considerable peripheral homeostatic expansion of these cells. To investigate the mechanisms behind, and consequences of, naive CD4(+) T cell homeostasis, we evaluated the age-dependent dynamics of the naive CD4(+) T cell subsets CD45RA(+)CD31(+) and CD45RA(+)CD31(−). Using both a cross-sectional and longitudinal study design, we measured the relative proportion of both subsets in individuals ranging from 22 to 73 years of age and quantified TCR excision circle content within those subsets as an indicator of proliferative history. Our findings demonstrate that waning thymic output results in a decrease in CD45RA(+)CD31(+) naive CD4(+) T cells over time, although we noted considerable individual variability in the kinetics of this change. In contrast, there was no significant decline in the CD45RA(+)CD31(−) naive CD4(+) T cell subset due to extensive peripheral proliferation. Our longitudinal data are the first to demonstrate that the CD45RA(+)CD31(+)CD4(+) subset also undergoes some in vivo proliferation without immediate loss of CD31, resulting in an accumulation of CD45RA(+)CD31(+) proliferative offspring. Aging was associated with telomere shortening within both subsets, raising the possibility that accumulation of proliferative offspring contributes to senescence of the naive CD4(+) T cell compartment in the elderly. In contrast, we observed retention of clonal TCR diversity despite peripheral expansion, although this analysis did not include individuals over 65 years of age. Our results provide insight into naive CD4(+) T cell homeostasis during aging that can be used to better understand the mechanisms that may contribute to immunosenescence within this compartment.